Chinese-Persian Translation Studies In Higher Educational Institutions In Iran With Market Demand (Journal of Namibian Studies : History Politics Culture, 2024)
Chinese is being widely recognized as the language of the future, presenting innumerable opportunities for commercial markets and exchanges. However, the studies in Chinese, especially in translation faculties, have not been able to keep up with this new demand. To address this issue, some research has been written that provides a historical overview of Chinese-Persian teaching studies and the translation of these two languages in Iran universities for both undergraduate and postgraduate courses. It describes the two universities in Tehran that teach Chinese-Persian and provide related translation courses, the subjects they offer, and the postgraduate course which are studied in both universities. The authors drew data for this paper from the researches of trainers and postgraduate students of Chinese-Persian translation in Iran, academic literature, and comparing the Iranian Student’s experience as Linguists, trainers, and translators in Non-Chinese language environments with the students in Chinese language environment like the author herself as a PhD of Chinese Philology in China with the privilege of the language environment. This paper provides detailed insights into the Chinese official university courses and their subjects, Chinese lecturer and student profiles, teaching methodologies, available materials, and methods of assessments. The authors in this paper offers a brief analysis of the relationship between the labor market and university training in Iran and describes the current state of research in this particular language combination. The paper concludes by highlighting the merits and shortcomings of training and research in Chinese-Persian translation in Iran and by considering future perspectives in the field.